A Retrospective Review of the Pennsylvania Justice Reinvestment Initiative - Wentling, Richard (The prison journal, 2025)
Justice reinvestment and the Justice Reinvestment Initiative (JRI) have been a focal point for criminal justice reform advocates since the enactment of federal legislation in 2010. With 40 states having implemented a JRI reinvestment policy or practice to date, the goal of many reinvestment strategies hinges on reducing prison populations. Pennsylvania was therefore uniquely situated for applying a reinvestment initiative as a state that was incarcerating more individuals per capita in the Northeast compared to neighboring states. This article reviews JRI's overall framework and intended evidence-based interventions utilizing a case study of Pennsylvania initiatives to assess the degree to which JRI strategies affected reform through 2023. Policy recommendations are offered based on the JRI application in Pennsylvania.